A Comprehensive Review on Niosomes as a Tool for Advanced Drug Delivery - Sharma, Shivani; Garg, Akash; Agrawal, Rutvi; Chopra, Himansu; Pathak, Devender (Pharmaceutical Nanotechnology, 2024)
Over the past few decades, advancements in nanocarrier-based therapeutic delivery have been significant, and niosomes research has recently received much interest. The self-assembled nonionic surfactant vesicles lead to the production of niosomes. The most recent nanocarriers, niosomes, are self-assembled vesicles made of nonionic surfactants with or without the proper quantities of cholesterol or other amphiphilic molecules. Because of their durability, low cost of components, largescale production, simple maintenance, and high entrapment efficiency, niosomes are being used more frequently. Additionally, they enhance pharmacokinetics, reduce toxicity, enhance the solubility of poorly water-soluble compounds, & increase bioavailability. One of the most crucial features of niosomes is their controlled release and targeted diffusion, which is utilized for treating cancer, infectious diseases, and other problems. In this review article, we have covered all the fundamental information about niosomes, including preparation techniques, niosomes types, factors influencing their formation, niosomes evaluation, applications, and administration routes, along with recent developments.
Keywords: Niosomes